2016
DOI: 10.1177/0956462415622866
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia among HIV patients in rural China during the HAART era

Abstract: The prevalence of anaemia among HIV patients receiving highly active antiretroviral therapy (HAART) in China has not been extensively studied. The purpose of this study was to estimate the prevalence of anaemia among HIV patients receiving HAART in China. This cross-sectional study was conducted based on data in routine record registers. Factors associated with anaemia were evaluated by logistic regression model. Among the 8632 HIV patients in this analysis, the overall prevalence of anaemia was 39.2%, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
10
13
2
Order By: Relevance
“…Lower CD4 cell count has been previously identified as a risk factor for anemia. The present study confirmed these findings, however we report much larger increased risks of anemia (HR = 8.40, 95%CI: 6.85, 10.51) and severe anemia (HR = 15.53, 95%CI:11.56-20.92) among PLWH with CD4 cell counts < 100 cells/mm 3 than have been previously reported [20][21][22][23][24]. Risks this large in magnitude suggest that additional screening and careful monitoring would potentially be useful among participants with CD4 levels < 100 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lower CD4 cell count has been previously identified as a risk factor for anemia. The present study confirmed these findings, however we report much larger increased risks of anemia (HR = 8.40, 95%CI: 6.85, 10.51) and severe anemia (HR = 15.53, 95%CI:11.56-20.92) among PLWH with CD4 cell counts < 100 cells/mm 3 than have been previously reported [20][21][22][23][24]. Risks this large in magnitude suggest that additional screening and careful monitoring would potentially be useful among participants with CD4 levels < 100 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 91%
“…Viral load ≥400 copies/ml 3314 (22) 338 ( Table 2). Among the 12,249 PLWH who were free of anemia at baseline, 265 developed chronic anemia (lasting for at least 6 months), during follow-up for an incidence of 0.46/100 person-years.…”
Section: Resultsmentioning
confidence: 99%
“…4 A study conducted in the very early years of HIV discovery had shown the overall prevalence of anemia to be about 28% among people with HIV infection in the pre-AIDS stage of the disease, whereas it could reach as high as 71% in the advanced or AIDS stage of the HIV disease. 9 The prevalence of anemia in this study was lower than the findings of studies conducted in China, 15 which was 39.2% and 52.3% in Arbaminch, 15 but it is higher than the studies conducted in Debretabor Hospital, 17 which was 23% and 16.2% in southwest Ethiopia. 13 In this study, those patients who had bedridden functional status were 5.5 times more anemic than those who are working.…”
Section: Discussioncontrasting
confidence: 76%
“…Patients who have less than two follow-up CD4 counts, transferred in and who had incomplete information about the outcome variable were excluded. The sample size was 422; it was calculated using sample size calculation formula taking confidence level=95%, power=80%, prevalence of anemia among HIV patients=52.3% 15 and by adding 10% non-response rate.…”
Section: Study Populationmentioning
confidence: 99%
“…Of the anemic study subjects, about 9% had severe anemia, 54% had moderate anemia, and 37% had mild anemia. The predominance of moderate type of anemia in the current study is in line with a study conducted at Tikur Anbessa Specialized Hospital, Addis Ababa [18] but it deviates from the findings reported in Wolita Sodo University, Sodo [36], Black Lion Hospital, Addis Ababa [12], Debre Tabor [37], and rural China [13], which reported high rate of mild anemia.…”
Section: Discussionsupporting
confidence: 66%